Prenatal care and uptake of HIV testing among pregnant women in Gambia: a cross-sectional study - Sanni Yaya; Olanrewaju Oladimeji; Kelechi Elizabeth Oladimeji; Ghose Bishwajit (BMC, 2020)
Abstract Background Improving the coverage of antenatal care is regarded as an important strategy to reduce the risks of maternal and child mortality in low income settings like Gambia. Nonetheless, a large number of countries in Africa, including Gambia, are struggling to attain an optimum level of healthcare utilization among pregnant women. The role of socioeconomic inequalities in maternal healthcare uptake has received little attention in Gambia. To address this evidence gap, the present study analyses nationally representative data to explore the socioeconomic inequalities in the use of maternal healthcare. Methods Data on women aged 15-49 years (n = 5351) were extracted from the latest round of Gambia Demographic and Health Survey in 2013 for this study. The outcome measures were early and adequate antenatal visit and HIV tests during the last pregnancy. Data were analyzed using descriptive and multivariate regression methods. Socioeconomic status was assessed through the women's education, type of employment, and household wealth quintile. Results From the total of 5351 participants included in the study, 38.7 and 78.8% of the women had early and adequate ANC visits respectively with a 65.4% HIV test coverage during ANC visits. The odds of early [OR = 1.30, 95% confidence interval (CI) =1.06, 1.59] and adequate [OR = 1.45, 95%CI = 1.15, 1.82] ANC visits were higher in the rural areas compared with urban. Women with secondary [OR = 1.24, 95%CI = 1.04, 1.48] and higher education [OR = 1.80, 95%CI = 1.20, 2.70] had higher odds of making early ANC visits. Women from richest wealth quintile households had significantly higher odds of having early [OR = 1.49, 95%CI = 1.14, 1.95] and adequate ANC visits [OR = 2.06, 95%CI = 1.48, 2.87], but not of having HIV tests. Having access to electronic media showed a positive association with adequate ANC visits [OR = 1.32, 95%CI = 1.08, 1.62] and with taking HIV test during ANC [OR = 1.48, 95%CI = 1.21, 1.80]. A fewer odds of having unintended child was associated with early ANC visit [OR = 0.70, 95%CI = 0.59, 0.84], but positively associated with taking HIV test [OR = 1.75, 95%CI = 1.42, 2.15]. Conclusion A large proportion of women in Gambia were not using antenatal care and HIV tests during pregnancy. There are important sociodemographic differences in using maternal healthcare services such as HIV testing during pregnancy. This calls for strategic direction to promote the utilization of these services.